The Principle of Moderation in Ibn Miskawaih’s Ethical Thought: Justice as the Virtue of the Soul - Taslim (Islamic Thought Review, 2025)
This article aims to analyze the principle of moderation (wasatiyyah) in Ibn Miskawaih’s ethical philosophy, with particular attention to his concept of justice as a central virtue of the soul. Drawing primarily on Tahdhīb al-Akhlāq wa Taṭhīr al-Aʿrāq, this study employs a qualitative library-based research method, utilizing conceptual and textual analysis of Ibn Miskawaih’s works alongside relevant secondary literature on Islamic ethics and virtue theory. The study seeks to address two main objectives: first, to examine Ibn Miskawaih’s understanding of justice within the framework of moral cultivation; and second, to explore the relationship between justice, love, and friendship in his ethical system. The findings demonstrate that Ibn Miskawaih conceives justice as the balanced mean between ẓulm (committing injustice by unlawfully taking others’ rights) and inẓilām (submitting to injustice by relinquishing one’s rights improperly). Justice, therefore, functions as an integrative virtue that harmonizes the faculties of the soul and sustains moral equilibrium. The study further reveals that Ibn Miskawaih’s ethical framework situates justice alongside simplicity, courage, and wisdom as foundational virtues essential for achieving moral perfection. This analysis highlights the enduring relevance of Ibn Miskawaih’s moderation-based ethics for contemporary discussions on moral balance, justice, and character formation in Islamic ethical thought.